Estrategias de afrontamiento y el funcionamiento familiar del grupo de autoayuda “camino a la vida” - Palacios Pineda, Alfredo Leonardo (2018)
This research was developed in the city of the self-help group "CAMINO A LA VIDA", with relevance in the psychological field. The objective is to analyze coping strategies in family functioning is a simple 30-man, whose age ranges from 21 to 74 years with an average of 40.83% and the mode of 21 years. This investigation is descriptive of cross section, quantitative. For the data collection and coping inventory (VCI) prepared by Videl and Tobal (1992) were used to identify the type of assessment and coping and the family functioning questionnaire (FF-SIL) prepared by Ortega de la Cuesta y Díaz ( 1999) to know the level of family functioning. After the application and tabulation of the results, it is concluded that 33% of the population presents behavioral coping strategies aimed at the situation; 20% present coordinated strategies directed to the emotion and cognitive directed to the situation. Passive 13% and 6.66% correspond to both behavioral and avoidant situations that show moderate family functioning in 56.67% followed by functional in 23.33%.